2015
DOI: 10.1080/10408398.2014.997866
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary polyphenols in the moderation of the inflammatory response in early stage colorectal cancer

Abstract: Current focus in colorectal cancer management is on reducing overall colorectal cancer mortality by increasing the number of early stage cancers diagnosed and treated with curative intent. There is good evidence that screening for colorectal cancer increases the number of early-stage cancers diagnosed and leads to a reduction of cancer specific mortality. Despite the success of the colorectal cancer screening programme in down-staging colorectal cancer, interval cancer rates are substantial and other strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 134 publications
1
19
0
Order By: Relevance
“…As a matter of fact, polyphenol-rich propolis extracts have been demonstrated to possess anti-inflammatory properties through regulation of I κ B- α /NF- κ B/p65 pathway by specifically delaying the ubiquitination of TRAF 6 [23]. Many other studies have also suggested that dietary polyphenols have many targets to attenuate inflammation, including but not limited to STAT, PI3K, and COX [24]. The exact target of M against inflammation is being explored in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, polyphenol-rich propolis extracts have been demonstrated to possess anti-inflammatory properties through regulation of I κ B- α /NF- κ B/p65 pathway by specifically delaying the ubiquitination of TRAF 6 [23]. Many other studies have also suggested that dietary polyphenols have many targets to attenuate inflammation, including but not limited to STAT, PI3K, and COX [24]. The exact target of M against inflammation is being explored in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging body of work on the potential impact of (poly)phenolic metabolites on age-related factors (inflammation, oxidative stress, glycation, dysbiosis) contributing to chronic diseases such as CRC [9][10][11][12][13][14]. Recently, the International Scientific Association for Probiotics and Prebiotic expanded the definition of the prebiotics to include (poly)phenolics as they are selectively metabolised by gut microbiota and release microbial bioactive molecules (including phenolic acids) that may confer local and systematic health benefits [15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…[57,58] As noted in the previous sections, quercetin, kaempferol, catechins, resveratrol, rutin, and their derivatives are known for their health benefits in humans and the prevention of various HDs (especially cancer, cardiovascular diseases, diabetes, obesity, liver disorder, and infectious diseases). [17,27,31,38,[59][60][61][62][63][64][65][66] Since fruits, especially apples, pears, apricots, cherries, berries, and grape, and vegetables, such as carrot, tomato, onion, garlic, cabbage, and celery, contain up to 200-300 mg of PCs per 100 g of their fresh weight, they can be used as dietary supplements of PCs. [67] The presence of these compounds in food and pharmaceutical industries has improved the quality of food and drugs.…”
Section: Which Compounds Received More Attention?mentioning
confidence: 99%